The incidence of low birth weight infants in pregnant mothers infected malaria - Setyowireni DK, Setyowireni DK (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1999)
Background: There are many pregnant mothers in malaria endemic area such as Purworejo suffering from anemia. It was considered a risk factor for pregnant mother to deliver low birth weight infants (LBWI).Objectives: The aim of the study is to investigate the correlation between pregnant mothers infected malaria with incidence of low birth weight infants (LBWI).Methods: The samples included pregnant mothers involved in an applied research at the Community Health and Nutrition Research Laboratory, Faculty of Medicine Gadjah Mada University in Purworejo, Central Java, who received vitamin A and zinc supplement. Five hundred and eighty three pregnant mothers were randomly selected during period of 1 year (1997). By using peripheral blood examination 160 pregnant mothers were found to be infected by malaria and 423 persons were not infected were used as control. Monthly visits were carried out to monitor the anemia status by Hemocue to determine the haemoglobin content and ferritin serum, anthropometry examination, health interview of gestation history using questionaires, and birth weight examination.Results: The prevalence of malaria on pregnant mothers was 10.6%. No characteristic difference of pregnant mothers in two groups statistically, except the ferritin level of pregnant mothers with malaria which was statistically lower (198.6 Âµg/dl) than non-infected mothers (617.1 Âµg/dl; p <0.001). The incidence of LBWI in Purworejo in 1997 was 5.3%. No significant difference of LBWI incidence was found in pregnant mothers with malaria (3.8%) and non infected mothers (1.7%; p = 0.13). The LBWI risk in pregnant mothers with malaria was two times higher than non infected mothers. And it is not significant statistically (OR=2.3; 95% CI=0.77-6.64). Multiple regression analysis showed that the important factor of LBWI incidence in pregnant mothers with malaria was gestational age (prematurity) (F=6.293; p = 0.012).Conclusion: The most important factor of LBWI in malaria infected pregnant mother is prematurity. We need to pay attention to them by considering iron deficiency.Â Key words: pregnant mother - malaria-ferritin serum - prematurity-low birth weight infants